Hubungan Komitmen Beragama Dengan Kesejahteraan Psikologis Pada Masyarakat Jakarta Usia Dewasa - Nelma, Hapsarini; Bintari, Dini Rahma; Nurwiyanti, Fivi (Jurnal Psikologi: PITUTUR, 2012)
This study focuses on the relationship between religious commitmentto  the  psychological  well-being.  The  research  was  done  because of  the increasing  phenomenon  of  religious  activity  in  the  city  as  a  result  of  the psychological burden caused by the problems in the city. This study used 124 subjects with a characteristic residence in Jakarta, the minimum high school education, aged 24-65 years. This study is a quantitative study using a  correlation  calculation  to  determine  the  relationship  between  two variables.  The  results  of  this  study  showed  a  significant  relationship between religious commitment to the psychological well-being